Efficacy of Contained Tissue Extraction for Minimizing Tissue Dissemination During Laparoscopic Hysterectomy and Myomectomy [66]. (May 2015) - Goggins, Emily R.; Greenberg, James A.; Cohen, Sarah L.; Morris, Stephanie Newman; Brown, Douglas N.; Einarsson, Jon Ivar
Abstract : INTRODUCTION: Tissue dissemination during uncontained laparoscopic electromechanical morcellation has raised safety concerns. This study sought to assess whether contained tissue extraction using electromechanical morcellators entirely within a bag is a safe, practical technique for preventing tissue spillage. METHODS: Patients undergoing laparoscopic or robotic hysterectomy or myomectomy at four hospitals were included. After surgical dissection, specimens to be extracted were placed into a containment bag with blue dye. The bag was insufflated intracorporeally, and electromechanical morcellation and extraction of tissue was performed. The containment system's integrity was evaluated visually for leakage of dye or tears in the bag. RESULTS: A total of 76 participants were included in the analysis (42 hysterectomy, 34 myomectomy). The average age was 43.16 years (±8.53), with an average body mass index (calculated as weight (kg)/[height (m)] 2 ) of 26.47 (±5.93). Thirty-three patients had a history of abdominal surgery. All cases employed a laparoscopic or robotic multiport technique. Morcellation took an average time of 30.2 minutes (±22.4). In one case, there was a tear before morcellation but no bag tears occurred during morcellation process. Spillage of dye or tissue was noted in seven cases, although containment bags were intact in each of these instances. There was one intraoperative complication with an estimated blood loss of 3600 mL and conversion to open radical hysterectomy. The median estimated blood loss was 50 mL (range 0–3600). The most common pathology finding was benign leiomyomas. CONCLUSION: Contained tissue extraction using electromechanical morcellation and intracorporeally insufflated bags may provide a safe alternative to uncontained morcellation by decreasing the spread of tissue in the peritoneal cavity while allowing for the traditional benefits of laparoscopy.